Indigenous Perspectives of Disability - Rivas Velarde, Minerva (Disability Studies Quarterly, 2018)
This article contributes to the discourse on disability from an indigenous perspective, an area which has not been investigated in any detail. It explores the perceptions of disability and lived experiences of 18 indigenous individuals with impairments from Australia, Mexico and New Zealand. The findings from this research suggest that participants from these countries share some common standpoints, particularly in relation to their disassociation from Western disability discourses and their common experiences of social oppression. This paper calls for further reflection about on-going colonisation and an in-depth analysis of the lack of attention given to this issue within the main models of disability.